Mystery behind the match: an undergraduate medical education–graduate medical education collaborative approach to understanding match goals and outcomes. Issue 1 (1st January 2016) - Nagler, Alisa; Engle, Deborah L.; Rudd, Mariah; Chudgar, Saumil M.; Weinerth, John L.; Kuhn, Catherine M.; Buckley, Edward; Grochowski, Colleen O'Connor
Abstract : Background: There is a paucity of information regarding institutional targets for the number of undergraduate medical education (UME) graduates being matched to graduate medical education (GME) programs at their home institutions. At our institution, the Duke University, the number of UME graduates matched to GME programs declined dramatically in 2011. To better understand why this decline may have happened, we sought to identify perceived quality metrics for UME and GME learners, evaluate trends in match outcomes and educational program characteristics, and explore whether there is an ideal retention rate for UME graduates in their home institutions' GME programs. Methods: We analyzed the number of Duke University UME graduates remaining at Duke for GME training over the past 5 years. We collected data to assess for changing characteristics of UME and GME, and performed descriptive analysis of trends over time to investigate the potential impact on match outcomes. Results: A one-sample t -test analysis showed no statistically significant difference in the number of Duke UME graduates who stayed for GME training. For both UME and GME, no significant changes in the characteristics of either program were found. Discussion: We created a process for monitoring data related to the characteristics or perceived quality of UME and GME programs and developed a shared understanding of what may impact match lists for both UME graduates and GME programs, leaving the Match somewhat less mysterious. While we understand the trend of graduates remaining at their home institutions for GME training, we are uncertain whether setting a goal for retention is reasonable, and so some mystery remains. We believe there is an invaluable opportunity for collaboration between UME and GME stakeholders to facilitate discussion about setting shared institutional goals.